Histopathology of Liver of Male Mice (Mus musculus L.) Hyperglycemia After Administration of Wheat Grass (Triticum aestivum L.) Juice - Yeni, Ratna (Jurnal Serambi Biologi, 2023)
Hyperglycemia is a condition when blood glucose levels increase due to insufficient insulin enzyme production to control blood sugar levels. Liver damage in conditions of hyperglycemia is caused by drug controversy in hepatocytes resulting in injury to cells. Wheat grass has the potential to cure hyperglycemia conditions. Flavonoid compounds found in wheat grass can repair liver cell damage due to hyperglycemia. This study aims to analyze the liver histopathology of hyperglycemic male mice (Mus musculus L.) after administration of wheatgrass juice (Triticum aestivum L.). This type of research was an experimental study using 24 male mice which were divided into four groups including, negative control group, positive control, treatment 1 and treatment 2. Examination of mice blood sugar using a glucometer, and preparation of mice liver histopathology using the paraffin method. Data analysis was carried out descriptively and presented in the form of pictures. The results of the study proved that the liver histopathology of P2 had a significant recovery compared to P1. Wheatgrass juice 100% was more effective in repairing the liver damage of hyperglycemic mice. Keywords: Hyperglycemia, Wheat Grass Juice, Hyperglycemia, Flavonoids.